HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS TEGALREJO - Ika May Yuni; Nurul Kurniati; Nurul Mahmudah (Journal of Innovation Research and Knowledge, 2025)
The high maternal and infant mortality rate in Indonesia is the main focus of solving health problems in Indonesia. Anemia in pregnant women is the main cause of bleeding and infection which are the main factors of maternal death. The purpose of the study was to determine the relationship between age and parity with the incidence of anemia in pregnant women at the Tegalrejo Health Center. The research method used was observational analytic correlation with a retrospective approach. The number of samples was 483, the sampling technique for control and cases was 1:1 with a simple random sampling system. The research instrument used a master table and medical records. Data analysis used the Chi Square test. The results of the analysis obtained the results of age p-value 0.002 (p <0.05) and parity p-value 0.103 (p> 0.05). The results showed that there was a relationship between age and the incidence of anemia in pregnant women and there was no relationship between parity and the incidence of anemia in pregnant women at the Tegalrejo Health Center. It is recommended that pregnant women can increase their insight by seeking information and utilizing health facilities about preventing anemia, for midwives by providing comprehensive care by providing IEC regarding the prevention of anemia in pregnant women